A língua portuguesa no vestibular dos povos indígenas no Paraná : conflitos e contradições entre políticas linguísticas e sociais de inclusão - Vitoriano, Luana de Souza (2016)
In 2001 the Act No. 13.134 was established as a historic and, especially, discursive event, considering that it was able to modify the educational order of Paraná State High School in socio-cultural, political and economic levels. The creation of this Act enabled conditions of emergence for the discursive practice of the Indigenous Peoples of Paraná's Vestibular implementation, a visibility space for the cultural and linguistic divergences of the contemporary indigenous subjects, and creates conditions so that the enunciations elaborated by the enrolled candidates reveal (or not) their proficiency in the written form of Portuguese Language. In face of theses singularities, that which enunciates about the vestibular and particularly, on the compositions, circumscribe itself under the aegis of a rarity and exteriority effect and accommodates a reading and interpretation gesture, which correlates theses enunciate properties to their dispersion and regularity effects. Therefore, as the research's guiding problematization we raise the following pieces of uneasiness: How does the exclusion by the language deployment creates (in)visibility spaces in the affirmative and linguistic policies, which fundament the discursive practice of the Indigenous Peoples of Paraná's Vestibular? And how does this same deployment create conditions of possibility in the (re)constitutions of the subjectivation processes in the ways of speaking of oneself manifested through/in the indigenous candidate's Portuguese Language proficiency? For this purpose, we proposed to analyze in this study, the archive consisting of 57 compositions from the II Indigenous Peoples Vestibular (2003), as well as the selection process itself in its singularities. We traced as a general objective of this study: to demonstrate the ways in which the emergence, (co)existence and possibility condition, which constitute this specific vestibular for indigenous peoples, create spaces of (in)visibilities the forms of perceiving and talking about indigenous peoples proficiency in higher education, and as specific objectives we seek to: I. Investigate the ways through which the Portuguese Language proficiency is able to capture the indigenous candidate/subject on the inside of Biopolitic formulations. II. Cover the forms in which the affirmative policies, as well as the linguistic policies, which constitute the indigenous vestibular selection process are designed under an imaginary exclusion and solidarity deployment. III. Clarify the reasons why the singularity of enunciations produced by contemporary indigenous subjects expresses subjectivation processes and resistance to non-indigenous social practices, and to the Portuguese Language functioning. The theoretical-analytical route establishes itself under the Discourse Analysis regime look, of French Brazilian line, prioritizing mainly the principles erected by Michel Foucault. We expect and have confidence in the relevance of this study due to the scarcity of researches in the scope of linguistiv-discursive questions related to the indigenous peoples of Parana, not only in order to leave a legacy to the forthcoming generation of researchers, but fundamentally to deepen findings which could lead to the comprehension of how the imaginary inclusion and solidarity deployment is able to subjectify the indigenous subjects to the practices that correspond mother Language and culture, as well as the practices referent to non-indigenous Language and culture. It was necessary to invest and contrive in this selection process, in order to surmise the ways in which the procedures understood and formulated as "inclusion" policies will actually be under the aegis of the functioning regime of a deployment governed by "exclusion".